Corrosive agent for testing austenitic grain size of high-carbon steel and method for pretreating sample for testing austenitic grain size of high-carbon steel
By providing a pre -treatment method that includes a corrosion agent including sodium acetate, sodium acetate, acetone, laurel alcohol and water, and high -carbon steel sample treatment methods, the problem of inaccurate identification in the crystal industry in the granularity test of the Aorer is solved, and it has achieved more accurate testing. result.
Patent Information
- Application Number
- CN202411456391.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-21
AI Technical Summary
Existing austenite grain size testing technology is difficult to accurately identify the grain boundaries of high-carbon steel, resulting in inaccurate test results.
Provides a high -carbon steel Octoba granular granular test, including acetic acid, sodium acetate, acetone, laurel, and water, combined with pre -sample treatment methods, including heat treatment, quenching, grinding throwing, rust removal and corrosion to ensure the crystal world Clear exposure.
By using this corrosive agent and sample pretreatment method, the grain boundaries of high carbon steel can be accurately identified, the accuracy of test results can be improved, and the rating standards of GB/6394-2017 can be met.
Smart Images

Figure CN119332243A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of austenite grain size testing, in particular to a corrosive agent for high carbon steel austenite grain size testing and a sample pretreatment method for high carbon steel austenite grain size testing. Background Art
[0002] Austenite grain size testing is an important test in materials science and metallurgical engineering. Its significance lies in evaluating the microstructural characteristics of materials at high temperatures, thereby predicting and controlling the properties of materials, such as strength, toughness, hardness, heat resistance and creep properties.
[0003] Austenite grain size refers to the size and distribution of austenite grains formed at high temperatures. The austenite grain size of steel can be determined by oxidation method. Specifically, the austenite grain size is displayed by using the characteristics that oxygen atoms diffuse into the crystal at high temperatures and the grain boundaries are preferentially oxidized. The specific principle is: since the chemical activity of metals is different at their grain boundaries and in the crystals, the metals on the grain boundaries are more active and easily oxidized. When the sample is heated at high temperature, the thickness of the oxides formed on the surface of the sample is different inside the grains and on the grain boundaries. The oxides on the grain boundaries are thicker than those inside the grains. Therefore, it is particularly necessary to make the sample have oxides only at the grain boundaries to display the grain boundaries, and to characterize the austenite grain size by displaying the oxides for easy determination and rating.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The purpose of the present invention is to provide a corrosive agent for testing the austenite grain size of high carbon steel and a method for pre-treating a sample for testing the austenite grain size of high carbon steel, which are beneficial to the accurate identification of grain boundaries.
[0006] The present invention is achieved in that:
[0007] In a first aspect, the present invention provides a corrosive agent for testing austenite grain size of high carbon steel, which comprises, by weight, 16-19 parts by weight of acetic acid, 1.2-1.8 parts by weight of sodium acetate, 8-12 parts by weight of acetone, 1.5-2.5 parts by weight of lauryl alcohol and 60-70 parts by weight of water.
[0008] In an optional embodiment, the composition comprises, by weight, 17.2-17.5 parts by weight of acetic acid, 1.4-1.6 parts by weight of sodium acetate, 9-11 parts by weight of acetone, 1.8-2.2 parts by weight of lauryl alcohol and 65.0-65.5 parts by weight of water.
[0009] In a second aspect, the present invention provides a method for pre-treating a sample for testing austenite grain size of high carbon steel, comprising:
[0010] The sample was heat treated at 860℃±10℃ for 1h, and then rapidly quenched in supercooled water;
[0011] The quenched sample is subjected to grinding and polishing in sequence to obtain a polished sample;
[0012] The polished sample is placed in a rust remover to remove rust, thereby obtaining a rust-removed sample;
[0013] The rust-removed sample is placed in the corrosive agent described in the above embodiment for corrosion to obtain a pre-treated sample.
[0014] In an optional embodiment, the corrosion time is 15-25 minutes.
[0015] In an optional embodiment, the rust remover is a hydrochloric acid solution with a mass fraction of 7%-8%.
[0016] In an optional embodiment, the rust removal time is 13-17 seconds.
[0017] In an alternative embodiment, the grinding depth is less than 10 μm.
[0018] In an optional embodiment, the polishing step includes: using a 3.5 μm polishing paste on a polishing cloth to polish the sample until the surface is smooth.
[0019] In an optional embodiment, before grinding and polishing, the process also includes: grinding the quenched sample with 600-grit sandpaper to remove iron oxide scale on the surface of the sample.
[0020] In an optional embodiment, the sample test surface is smooth without curling or burrs;
[0021] And / or, the samples are cleaned and dried after polishing, rust removal and corrosion.
[0022] The present invention has the following beneficial effects:
[0023] The acetic acid and sodium acetate in this application constitute an acetic acid-sodium acetate buffer solution, which can keep the pH of the corrosive agent relatively stable and avoid excessive corrosion while providing an acidic environment and promoting the corrosion of the sample test surface; acetone can be used as a solvent to dissolve grease and organic matter, which is beneficial to keep the sample package clean; lauryl alcohol can reduce surface tension, improve the wettability and emulsification ability of the sample surface, and is beneficial to the full and uniform contact between the corrosive agent and the sample surface, thereby improving the uniformity of corrosion. In this application, the acetic acid-sodium acetate buffer solution and acetone and lauryl alcohol work together, and at a suitable concentration, are applied to the corrosion of high-carbon steel samples, which is beneficial to the accurate identification of grain boundaries. After pretreatment, the samples can be rated with reference to GB / 6394-2017. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0025] Figure 1 The microscopic images (100x and 500x) of the sample 1 after pretreatment in Example 1;
[0026] Figure 2 The microscopic images (100x and 1000x) of the sample 2 after pretreatment in Example 1;
[0027] Figure 3 This is a microscopic picture (100x) of the sample after pretreatment in Comparative Example 1;
[0028] Figure 4 This is a microscopic image (100x) of the sample after pretreatment in Comparative Example 2;
[0029] Figure 5 This is a microscopic image (100x) of the sample after pretreatment in Comparative Example 3;
[0030] Figure 6 This is a microscopic image (100x) of the sample after pretreatment in Comparative Example 4;
[0031] Figure 7 This is a microscopic image (100x) of the sample after pretreatment (corrosion for 5 minutes) in Comparative Example 5;
[0032] Figure 8 This is a microscopic image (100x) of the sample after pretreatment (corrosion for 15 min) in Comparative Example 5;
[0033] Fig. 9 This is a microscopic image (100x) of the sample after pretreatment in Comparative Example 6;
[0034] Fig.10 This is a microscopic image (100x) of the sample after pretreatment in Comparative Example 7;
[0035] Fig.11 This is a microscopic image (100x) of the sample after pretreatment in Comparative Example 8. DETAILED DESCRIPTION
[0036] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0037] An embodiment of the present invention provides a corrosive for testing austenite grain size of high carbon steel, which comprises, by weight, 16-19 parts by weight of acetic acid, 1.2-1.8 parts by weight of sodium acetate, 8-12 parts by weight of acetone, 1.5-2.5 parts by weight of lauryl alcohol and 60-70 parts by weight of water.
[0038] The acetic acid and sodium acetate in the present application constitute an acetic acid-sodium acetate buffer solution, which can keep the pH of the corrosive agent relatively stable and avoid transitional corrosion while providing an acidic environment and causing the sample test surface to be corroded; acetone can be used as a solvent to dissolve grease and organic matter, which is beneficial to keeping the sample package surface clean; lauryl alcohol can reduce surface tension, improve the wettability and emulsification ability of the sample surface, and is beneficial to the full and uniform contact between the corrosive agent and the sample surface, improving the uniformity of corrosion, and can also increase the stability of the solution and delay the shelf life. In the present application, the acetic acid-sodium acetate buffer solution and acetone and lauryl alcohol work together, and at a suitable concentration, it is applied to the corrosion of high-carbon steel samples, which is beneficial to the accurate identification of grain boundaries.
[0039] In an optional embodiment, the composition comprises, by weight, 17.2-17.5 parts by weight of acetic acid, 1.4-1.6 parts by weight of sodium acetate, 9-11 parts by weight of acetone, 1.8-2.2 parts by weight of lauryl alcohol and 65.0-65.5 parts by weight of water.
[0040] Optimizing the composition of the etchant is beneficial to avoiding unclear or incomplete exposure of grain boundaries caused by excessive or insufficient corrosion, and is more conducive to accurate identification of grain boundaries.
[0041] The embodiment of the present invention also provides a method for pre-treating a sample for testing austenite grain size of high carbon steel, comprising:
[0042] The sample was heat treated at 860℃±10℃ for 1h, and then rapidly quenched in supercooled water;
[0043] The quenched sample is subjected to grinding and polishing in sequence to obtain a polished sample;
[0044] The polished sample is placed in a rust remover to remove rust, thereby obtaining a rust-removed sample;
[0045] The rust-removed sample is placed in the corrosive agent described in the above embodiment for corrosion to obtain a pre-treated sample.
[0046] The heat treatment steps are carried out in accordance with the oxidation method of GB / 6394-2017, and grinding and polishing are performed to remove the oxides inside the grains, and then rust removal and corrosion are performed in sequence to expose the grain boundaries clearly.
[0047] In an optional implementation, the corrosion time is 15-25 minutes. If the corrosion time is too short or too long, insufficient corrosion or excessive corrosion may occur, which is not conducive to accurate identification of grain boundaries.
[0048] In an optional embodiment, the rust remover is a hydrochloric acid solution with a mass fraction of 7%-8%.
[0049] If rust removal is not performed, part of the sample surface will be covered with rust. Prolonging the corrosion time to remove the surface rust may cause over-corrosion. In severe cases, the tissue will be corroded out, which is also not conducive to the accurate identification of grain boundaries. Therefore, a special rust removal step is set.
[0050] In an optional implementation manner, the rust removal time is 13-17 seconds, and the rust removal time is short to avoid excessive corrosion.
[0051] In an optional implementation, the grinding and polishing depth is less than 10 μm. Too great a grinding and polishing depth may cause the grain boundaries to be shallow, thereby making it impossible to accurately identify the grain boundaries.
[0052] In an optional embodiment, the polishing step includes: using a 3.5 μm polishing paste on a polishing cloth to polish the sample until the surface is smooth.
[0053] In an optional embodiment, before grinding and polishing, the process also includes: grinding the quenched sample with 600-grit sandpaper to remove iron oxide scale on the surface of the sample.
[0054] After quenching and cooling, the sample is first polished on 600# mesh sandpaper to remove the thick residual iron oxide scale (if there is no thick iron oxide scale, this step can be omitted), and then polished on 2000# mesh sandpaper with a depth of less than 10μm, and then polished on a polishing cloth with 3.5μm polishing paste until the surface is smooth. If the sandpaper is too coarse, the surface austenite oxide grain boundary will be polished away, resulting in test failure. If the sandpaper is too fine, it is difficult to completely remove the surface iron oxide scale and the austenite grains are difficult to show. During specific polishing, the sample can be observed under a microscope after the preliminary polishing and pretreatment. If the grain boundary cannot meet the requirements, the polishing depth is gradually increased and the polishing depth is fine-tuned. If not specified, the micrographs in the subsequent embodiments and comparative examples are all micrographs of the most complete and clear grain boundaries that can be observed under the corresponding conditions.
[0055] In an optional embodiment, the sample test surface is smooth and has no curling or burrs; specifically, the wire can be cut into small segments of 20 mm, and the sample test surface is polished by a coarse grinder, 150# mesh sandpaper, 600# mesh sandpaper, 1200# mesh sandpaper, and 2000# mesh sandpaper to be smooth and free of curling or burrs.
[0056] In an optional embodiment, the sample is cleaned and dried after polishing, rust removal and corrosion.
[0057] The features and properties of the present invention are further described in detail below in conjunction with the examples. The concentrations involved in the following examples and comparative examples, unless otherwise specified, refer to mass fractions.
[0058] Example 1
[0059] This embodiment provides a method for pre-treating a sample for testing austenite grain size of high carbon steel, which specifically comprises the following steps:
[0060] 1. Cut the wire into small sections of 20 mm, and grind and polish them using a coarse grinder, 150# grit sandpaper, and 600# grit sandpaper to make the surface smooth without curling or burrs.
[0061] 2. Heat the prepared sample at 860℃±10℃ according to the oxidation method specified in GB / 6394-2017, keep it warm for 1h, and quickly quench it with supercooled water.
[0062] 3. After quenching and cooling, wipe off the thicker iron oxide scale on the surface of the sample, polish off the remaining thicker iron oxide scale on 600# grit sandpaper (in other embodiments, if there is no thicker iron oxide scale, this step can be omitted), grind and polish on 2000# grit sandpaper to a depth of less than 10μm, and then use 3.5μm polishing paste on the polishing cloth to polish until the surface is smooth.
[0063] 4. Spray the polished surface with alcohol, blow dry the surface with a hair dryer, put it into the rust remover, soak it in the rust remover for 15 seconds, take it out, spray alcohol and blow dry the surface. The rust remover is a hydrochloric acid solution with a mass fraction of 7.6%.
[0064] 5. Soak in the corrosion solution for 20 minutes, take it out, spray alcohol and blow dry the surface. Two experiments were conducted on Example 1 to obtain Sample 1 and Sample 2. The corrosion effects under the microscope at 100x and 500x are as follows: Figure 1 and Figure 2 shown.
[0065] The preparation of the etching solution includes: weighing 46g of acetic acid and 4g of sodium acetate, adding 164g of water to dissolve to obtain an acetic acid-sodium acetate buffer solution;
[0066] Take 80g of acetic acid-sodium acetate buffer solution, add 10g of acetone, add 2g of lauryl alcohol, add 4g of water, and dissolve to obtain the etching solution.
[0067] Comparative Example 1
[0068] This comparative example provides a method for pre-treating a sample for testing austenite grain size of high carbon steel, which specifically comprises the following steps:
[0069] 1. Cut the wire into small sections of 20 mm, and grind and polish them using a coarse grinder, 150# grit sandpaper, and 600# grit sandpaper to make the surface smooth without curling or burrs.
[0070] 2. Heat the prepared sample at 860℃±10℃ according to the oxidation method specified in GB / 6394-2017, keep it warm for 1h, and quickly quench it with supercooled water.
[0071] 3. After quenching and cooling, wipe off the thicker iron oxide scale on the surface of the sample, polish off the remaining thicker iron oxide scale on 600# grit sandpaper (in other embodiments, if there is no thicker iron oxide scale, this step can be omitted), grind and polish on 2000# grit sandpaper to a depth greater than 10μm and less than 30μm, and then use 3.5μm polishing paste on the polishing cloth to polish until the surface is smooth.
[0072] 4. After spraying the polished surface with alcohol, use a hair dryer to dry the surface. First, put a small amount of cotton in the crucible to absorb the corrosion reagent, then put the sample on the cotton with the corrosion reagent, soak them in the crucible for 20 minutes, take them out, spray alcohol and blow dry the surface. The corrosion effect under the microscope at 100x is as follows: Figure 3 The preparation of the etching solution includes: weighing 46g of acetic acid and 4g of sodium acetate, adding 164g of water to dissolve to obtain an acetic acid-sodium acetate buffer solution;
[0073] Take 80g of acetic acid-sodium acetate buffer solution 80% + hydrochloric acid (38%) 4% + acetone 10% + detergent 2% + distilled water 4% and dissolve them to obtain the etching solution.
[0074] Comparative Example 2
[0075] This comparative example provides a method for pre-treating a sample for testing austenite grain size of high carbon steel, which specifically comprises the following steps:
[0076] 1. Cut the wire into small sections of 20 mm, and grind and polish them using a coarse grinder, 150# grit sandpaper, and 600# grit sandpaper to make the surface smooth without curling or burrs.
[0077] 2. Heat the prepared sample at 860℃±10℃ according to the oxidation method specified in GB / 6394-2017, keep it warm for 1h, and quickly quench it with supercooled water.
[0078] 3. After quenching and cooling, wipe off the thicker iron oxide scale on the surface of the sample, polish off the remaining thicker iron oxide scale on 600# grit sandpaper (in other embodiments, if there is no thicker iron oxide scale, this step can be omitted), grind and polish on 2000# grit sandpaper to a depth greater than 10μm and less than 30μm, and then use 3.5μm polishing paste on the polishing cloth to polish until the surface is smooth.
[0079] 4. After spraying the polished surface with alcohol, use a hair dryer to dry the surface. First, put a small amount of cotton in the crucible to absorb the corrosion reagent, then put the sample on the cotton with the corrosion reagent, soak them in the crucible for 20 minutes, take them out, spray alcohol and blow dry the surface. The corrosion effect under the microscope at 100x is as follows: Figure 4 The preparation of the etching solution includes: weighing 46g of acetic acid and 4g of sodium acetate, adding 164g of water to dissolve to obtain an acetic acid-sodium acetate buffer solution;
[0080] Take 80% acetic acid-sodium acetate buffer solution + 4% hydrochloric acid (38%) + 10% ethanol + 2% lauryl alcohol + 4% distilled water, and dissolve them to obtain the etching solution.
[0081] Comparative Example 3
[0082] This comparative example provides a method for pre-treating a sample for testing austenite grain size of high carbon steel, which specifically comprises the following steps:
[0083] 1. Cut the wire into small sections of 20 mm, and grind and polish them using a coarse grinder, 150# grit sandpaper, and 600# grit sandpaper to make the surface smooth without curling or burrs.
[0084] 2. Heat the prepared sample at 860℃±10℃ according to the oxidation method specified in GB / 6394-2017, keep it warm for 1h, and quickly quench it with supercooled water.
[0085] 3. After quenching and cooling, wipe off the thicker iron oxide scale on the surface of the sample, polish off the remaining thicker iron oxide scale on 600# grit sandpaper (in other embodiments, if there is no thicker iron oxide scale, this step can be omitted), grind and polish on 2000# grit sandpaper to a depth greater than 10μm and less than 30μm, and then use 3.5μm polishing paste on the polishing cloth to polish until the surface is smooth.
[0086] 4. After spraying the polished surface with alcohol, use a hair dryer to dry the surface. First, put a small amount of cotton in the crucible to absorb the corrosion reagent, then put the sample on the cotton with the corrosion reagent, soak them in the crucible for 20 minutes, take them out, spray alcohol and blow dry the surface. The corrosion effect under the microscope at 100x is as follows: Figure 5 The preparation of the etching solution includes: weighing 46g of acetic acid and 4g of sodium acetate, adding 164g of water to dissolve to obtain an acetic acid-sodium acetate buffer solution;
[0087] Take 80% acetic acid-sodium acetate buffer solution + 4% hydrochloric acid (38%) + 10% acetone + 2% lauryl alcohol + 4% distilled water, and dissolve them to obtain the etching solution.
[0088] Comparative Example 4
[0089] This comparative example provides a method for pre-treating a sample for testing austenite grain size of high carbon steel, which specifically comprises the following steps:
[0090] 1. Cut the wire into small sections of 20 mm, and grind and polish them using a coarse grinder, 150# grit sandpaper, and 600# grit sandpaper to make the surface smooth without curling or burrs.
[0091] 2. Heat the prepared sample at 860℃±10℃ according to the oxidation method specified in GB / 6394-2017, keep it warm for 1h, and quickly quench it with supercooled water.
[0092] 3. After quenching and cooling, wipe off the thicker iron oxide scale on the surface of the sample, polish off the remaining thicker iron oxide scale on 600# grit sandpaper (in other embodiments, if there is no thicker iron oxide scale, this step can be omitted), grind and polish on 2000# grit sandpaper to a depth of less than 10μm, and then use 3.5μm polishing paste on the polishing cloth to polish until the surface is smooth.
[0093] 4. After spraying the polished surface with alcohol, use a hair dryer to dry the surface and put it into the corrosion reagent. First put a small amount of cotton in the crucible to absorb the corrosion reagent, then put the sample on the cotton with the corrosion reagent, soak them in the crucible for 20 minutes, take them out, spray alcohol and blow dry the surface. The corrosion effect under the microscope at 100x is as follows Figure 6 The preparation of the etching solution includes: weighing 46g of acetic acid and 4g of sodium acetate, adding 164g of water to dissolve to obtain an acetic acid-sodium acetate buffer solution;
[0094] Take 80g of acetic acid-sodium acetate buffer solution, add 10g of acetone, add 2g of lauryl alcohol, add 4g of water, and dissolve to obtain the etching solution.
[0095] Comparative Example 5
[0096] This comparative example provides a method for pre-treating a sample for testing austenite grain size of high carbon steel, which specifically comprises the following steps:
[0097] 1. Cut the wire into small sections of 20 mm, and grind and polish them using a coarse grinder, 150# grit sandpaper, and 600# grit sandpaper to make the surface smooth without curling or burrs.
[0098] 2. Heat the prepared sample at 860℃±10℃ according to the oxidation method specified in GB / 6394-2017, keep it warm for 1h, and quickly quench it with supercooled water.
[0099] 3. After quenching and cooling, wipe off the thicker iron oxide scale on the surface of the sample, polish off the remaining thicker iron oxide scale on 600# grit sandpaper (in other embodiments, if there is no thicker iron oxide scale, this step can be omitted), grind and polish on 2000# grit sandpaper to a depth of less than 10μm, and then use 3.5μm polishing paste on the polishing cloth to polish until the surface is smooth.
[0100] 4. After spraying the polished surface with alcohol, use a hair dryer to dry the surface and put it into the corrosion reagent. First, put a small amount of cotton in the crucible to absorb the corrosion reagent, and then put two samples on the cotton with the corrosion reagent. Soak them in the crucible for 5 minutes and 15 minutes respectively, then take them out, spray alcohol and blow dry the surface. The corrosion effect under a microscope at 100x is as follows Figure 7 (immersion for 5 minutes) and 8 (immersion for 15 minutes) are shown. The preparation of the etching solution includes: taking 100 ml of ethanol, 5 g of boric acid + 0.3 ml of nitric acid (69%) + 0.9 ml of hydrochloric acid (38%), and dissolving them to obtain the etching solution.
[0101] Comparative Example 6
[0102] This comparative example provides a method for pre-treating a sample for testing austenite grain size of high carbon steel, which specifically comprises the following steps:
[0103] 1. Cut the wire into small sections of 20 mm, and grind and polish them using a coarse grinder, 150# grit sandpaper, and 600# grit sandpaper to make the surface smooth without curling or burrs.
[0104] 2. Heat the prepared sample at 860℃±10℃ according to the oxidation method specified in GB / 6394-2017, keep it warm for 1h, and quickly quench it with supercooled water.
[0105] 3. After quenching and cooling, wipe off the thicker iron oxide scale on the surface of the sample, polish off the remaining thicker iron oxide scale on 600# grit sandpaper (in other embodiments, if there is no thicker iron oxide scale, this step can be omitted), grind and polish on 2000# grit sandpaper to a depth of less than 10μm, and then use 3.5μm polishing paste on the polishing cloth to polish until the surface is smooth.
[0106] 4. After spraying the polished surface with alcohol, use a hair dryer to dry the surface and put it into the corrosion reagent. First put a small amount of cotton in the crucible to absorb the corrosion reagent, then put the sample on the cotton with the corrosion reagent, soak them in the crucible for 20 minutes, take them out, spray alcohol and blow dry the surface. The corrosion effect under the microscope at 100x is as follows Fig. 9 The preparation of the etching solution includes: measuring 2.4 ml of 0.2 mol / L disodium hydrogen phosphate and 1.24 ml of 0.1 mol / L citric acid to obtain a disodium hydrogen phosphate-citric acid buffer solution;
[0107] Take 80g of disodium hydrogen phosphate-citric acid buffer solution, add 10g of acetone, 2g of lauryl alcohol, and 4g of water, and dissolve to obtain the etching solution.
[0108] Comparative Example 7
[0109] This comparative example provides a method for pre-treating a sample for testing austenite grain size of high carbon steel, which differs from Example 1 only in that: the preparation of the etching solution includes: weighing 46g of acetic acid and 4g of sodium acetate, adding 164g of water to dissolve to obtain an acetic acid-sodium acetate buffer solution;
[0110] Take 50g of acetic acid-sodium acetate buffer solution, add 15g of acetone, add 4g of lauryl alcohol, add 7g of water, and dissolve to obtain the etching solution. The etching effect of the sample under a microscope at 100x is as follows Fig.10 shown.
[0111] Comparative Example 8
[0112] This comparative example provides a method for pre-treating a sample for testing austenite grain size of high carbon steel, which differs from Example 1 only in that: the preparation of the etching solution includes: weighing 46g of acetic acid and 4g of sodium acetate, adding 164g of water to dissolve to obtain an acetic acid-sodium acetate buffer solution;
[0113] Take 100g of acetic acid-sodium acetate buffer solution, add 8g of acetone, add 1g of lauryl alcohol, add 4g of water, and dissolve to obtain the etching solution. The etching effect of the sample under a microscope at 100x is as follows Fig.11 shown.
[0114] By comparing the above-mentioned comparative examples 1 and 3 and the comparative examples 2 and 3, it can be seen that the combination of acetone and lauryl alcohol in the etching reagent has the best grain boundaries of austenite grain size compared with acetone and detergent or ethanol and lauryl alcohol, but there is a case where the grain boundaries are shallow.
[0115] Compared with Example 1, although Comparative Example 4 changes the grinding and polishing depth to make the grain boundary clearer than that of Comparative Example 3, it is still shallower than that of Example 1, and there are still many iron oxide scale attachments, which affects the rating judgment.
[0116] Compared with Example 1, the type of acid in the etchant was adjusted according to Figure 7 and Figure 8 , the corrosive agent in Example 5 will cause tissue to appear, thereby affecting the rating judgment.
[0117] It can be seen from the comparison between Example 1 and Comparative Examples 6, 7 and 8 that the adjustment of the components of the etching solution and the dosage of each component will lead to the deterioration of the etching effect.
[0118] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A corrosive agent for testing austenite grain size of high carbon steel, characterized in that: Calculated by weight, the composition comprises 16-19 parts by weight of acetic acid, 1.2-1.8 parts by weight of sodium acetate, 8-12 parts by weight of acetone, 1.5-2.5 parts by weight of lauryl alcohol and 60-70 parts by weight of water.
2. The corrosive agent for testing austenite grain size of high carbon steel according to claim 1, characterized in that: Calculated by weight, the composition comprises 17.2-17.5 parts by weight of acetic acid, 1.4-1.6 parts by weight of sodium acetate, 9-11 parts by weight of acetone, 1.8-2.2 parts by weight of lauryl alcohol and 65.0-65.5 parts by weight of water.
3. A method for pre-treating a sample for testing austenite grain size of high carbon steel, characterized in that: include: The sample was heat treated at 860℃±10℃ for 1h, and then rapidly quenched in supercooled water; The quenched sample is subjected to grinding and polishing in sequence to obtain a polished sample; The polished sample is placed in a rust remover to remove rust, thereby obtaining a rust-removed sample; The rust-removed sample is placed in the corrosive agent of claim 1 for corrosion to obtain a pre-treated sample.
4. The method for pre-treating a sample for testing austenite grain size of high carbon steel according to claim 3, characterized in that: The corrosion time is 15-25min.
5. The method for pre-treating a sample for testing austenite grain size of high carbon steel according to claim 3, characterized in that: The rust remover is a hydrochloric acid solution with a mass fraction of 7%-8%.
6. The method for pre-treating a sample for testing austenite grain size of high carbon steel according to claim 3, characterized in that: The rust removal time is 13-17s.
7. The method for pre-treating a sample for testing austenite grain size of high carbon steel according to claim 3, characterized in that: The grinding and polishing depth is less than 10μm.
8. The method for pre-treating a sample for testing high carbon steel austenite grain size according to claim 3, characterized in that: The polishing step includes: using 3.5 μm polishing paste on a polishing cloth to polish the sample until the surface is smooth.
9. The method for pre-treating a sample for testing austenite grain size of high carbon steel according to claim 3, characterized in that: Before grinding and polishing, the quenched sample is polished with 600-grit sandpaper to remove the iron oxide scale on the surface of the sample.
10. The method for pre-treating a sample for testing austenite grain size of high carbon steel according to claim 3, characterized in that: The test surface of the sample is smooth without curling or burrs; And / or, the samples are cleaned and dried after polishing, rust removal and corrosion.